Entrepreneurial assistance for down syndrome children and caregivers in the DSI community - Innas Rovino Katuruni; Rahma Nur Praptiwi; Sri Isti Untari; Iftita Rahmi; Tika Dwi Ariyanti (Universitas Muhammadiyah Magelang, 2022)
A vulnerable population, people with disabilities frequently face discrimination in the workplace. They frequently struggle to find employment in the formal sector because there aren't enough workplace amenities to support them and there aren't enough positions that match their skills. Because there aren't many jobs available in Indonesia for those with disabilities, starting a business is an excellent career option. This community service program aims to provide training and assistance for people with disabilities, especially people with Down syndrome and their caregiver who are members of the Down Syndrome Indonesia (DSI) community. This activity was conducted in three stages, including webinars, psychological testing to identify participants' strengths, workshops, and entrepreneurship mentoring. The results of this program were increased knowledge and skills of people with Down syndrome and their caregivers regarding interests and talents and the process of starting and developing a business. Thus, it is hoped that businesses built by people with Down syndrome and their caregivers can last a long time so that they can achieve economic independence.